Performance analysis of heat exchanger for fluids with variable properties. (February 2019) - Guo, Jiangfeng; Cui, Xinying; Zhang, Haiyan; Huai, Xiulan; Cheng, Keyong
Abstract: The Span and Wagner's state equation and the segmental design were employed to accommodate the sharp changes of thermophysical properties of supercritical CO2 (S-CO2 ). The distributions of some important parameters along heat exchanger were discussed. The total entransy dissipation decreases as the coordination between heat transfer rate and temperature difference improves when the total heat transfer rate is fixed and divided evenly, which agrees with the equipartition principle of entransy dissipation. A new dimensionless temperature difference, which comprehensively considers the effectiveness and exchanger area, was proposed without the assumption of fixed thermophysical properties. The new evaluation criterion could represent the 'efficiency' of heat exchanger. The present work may be helpful for the design and optimization of heat exchanger using fluids with sharply variable properties.